Anti‐apoptotic effects of adipose‐derived adherent stromal cells in mesenchymal stem cells exposed to oxidative stress. (19th June 2018) - Shin, Sunhye; Choi, Jung‐Won; Lim, Soyeon; Lee, Seahyoung; Jun, Eun‐Young; Sun, Hyun‐Min; Kim, Il‐Kwon; Lee, Hoon‐Bum; Kim, Sang Woo; Hwang, Ki‐Chul
Abstract : Adipose‐derived stromal vascular fractions (SVFs) are a heterogeneous collection of cells, and their regenerative modality has been applied in various animal experiments and clinical trials. Despite the attractive advantages of SVFs in clinical interventions, the recent status of clinical studies involving the application of SVFs in many diseases has not been fully evaluated. Mesenchymal stem cells (MSCs) are multipotent stromal cells that can differentiate into a variety of cell types despite their low numbers in heart tissue. Here, we sought to determine if SVF implantation into impaired heart tissue affected endogenous MSCs in the heart. Therefore, we investigated the expression levels of proteins associated with oxidation, inflammation, and apoptosis in MSCs co‐cultured with adipose‐derived adherent stromal cells (ADASs) from 6 donors' SVFs under oxidative stress conditions for their roles in many physiological processes in the heart. Interestingly, p53 pathway proteins and mitogen‐activated protein kinase (MAPK) signalling pathway components were up‐regulated by H2 O2 but exhibited a downward trend in MSCs co‐cultured with ADASs. These data suggest that ADASs may inhibit oxidative stress‐induced apoptosis in MSCs via the p53 and MAPK pathways. Our findings also suggest that the positive effects of SVF implantation into damaged heart tissue may be attributed to the various responses of MSCs. This finding may provide new insights for the clinical application of adipose‐derived SVF transplantation in cardiac diseases. Significance of the study: We investigated the expression levels of proteins associated with oxidation, inflammation, and apoptosis in MSCs co‐cultured with isolated ADASs from 6 donors' SVFs under oxidative stress conditions. Our results imply that isolated ADASs from SVFs may inhibit oxidative stress‐induced cell cycle arrest and/or apoptosis in MSCs via a p53‐dependent pathway. Furthermore, we identified an anti‐apoptotic mechanism involving oxidative stress‐induced apoptosis by adipose‐derived ADASs in MSCs for the first time. Our findings suggest that the positive effects of SVF implantation into damaged heart tissue may be attributed to the various actions of MSCs.